Students' Mathematical Attitudes: A Systematic Mapping Study - Trisno Santoso; Nining Haerunisa (Noumerico: Journal of Technology in Mathematics Education, 2023)
This article is preliminary research that explores the results of studies conducted on students' mathematical attitudes using Systematic Mapping Study (SMS). The purpose of this Mapping is to discuss any mathematical attitude topic that is being reviewed and studied. This research uses qualitative methods using a study library. The search was carried out on the Scopus database with 36 articles used in 2014-2022 publications published in the form of scientific journals included in the inclusion criteria. The results of this SMS show an overview of opportunities to explore new topics in students' Mathematical Attitudes or utilise existing issues regarding the most significant focus of mathematics education: gender, student attitudes, self-concept, attitudes to mathematics, gender differences, and mathematical performance. The trends from several countries studied are China, the United States, the United Kingdom, Italy, Spain, Germany, the Russian Federation, France, and Canada